Development of algorithms for ship engine-propeller matching - Teo, Wei Loon (2016)
In the preliminary design of a ship, engine-propeller matching was considered as one of the problems that naval architect faced. The problem can be done through traditional method but it takes a lot of time and have a lower accuracy and hence, this report introduced using MATLAB algorithms to reduce the time taken while maintaining the accuracy of the results. In general, there was four main type of problems in engine-propeller matching namely; Finding optimum propeller diameter with given speed, optimum rotation speed with given propeller diameter, optimum diameter with given power and rotation speed and maximum bollard pull. Flowcharts and MATLAB algorithms were developed to address the four different type of problems in propeller-engine matching. Different ship data was performed on the algorithms. Algorithms results obtained were consistent with the ship data results.